Hubungan Tingkat Stres dengan Kadar Glukosa Darah Puasa pada Pasien DM Tipe 2 di RSUD Sanjiwani Gianyar - Ni Luh Putu Dewi Pridani; Putu Asih Primatanti; Sri Ratna Dewi (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2024)
[Relationship between Stress Levels and Fasting Blood Glucose in Type 2 DM Patients at Sanjiwani Hospital Gianyar] Diabetes mellitus is a chronic dissease that causes effects on the metabolic system. In a stressful situation, there is excessive production of the cortisol, which reduces the body's sensitivity to insulin. Cortisol can make glucose difficult to enter cells and accumulate in the blood, increasing blood glucose levels. The purpose of this research is to analyze the correlation between stress levels and fasting blood glucose levels in type 2 diabetes mellitus patients at Sanjiwani Hospital, Gianyar. The method used analytical observational with a cross sectional approach using 95 sample of patients with type 2 diabetes mellitus in Sanjiwani Hospital and using a consecutive sampling technique. Data collection using primary sources : a diabetic distress scale questionnaire and secondary data (medical records). Data analysis by spearman test. The characteristics of the research subjects were that the majority the late elderly age range (44.2%), the majority of patients were male (53.7%), their highest education was high school (44.2%), as many as (31.6%) worked as self-employed, and patients had no family history of DM (69.5%). The stress level of the subjects in this study was dominated by severe stress levels (45.3%) almost of subjects' glucose was high (74.7%). The results of the Spearman correlation test analysis obtained a significance value of 0.00 with a significance level of 0.05, which means there is a correlation between stress levels and fasting blood sugar levels in type 2 DM patients at Sanjiwani Hospital. The correlation coefficient figure shows 0.373, meaning the strength of the relationship is weak. The correlation coefficient positive so that the corellation between the variables is one direction, meaning the stress can increase the blood glucose levels.